2018
DOI: 10.1103/physrevb.98.214107
|View full text |Cite
|
Sign up to set email alerts
|

Charge state switching of the divacancy defect in 4H -SiC

Abstract: Optical charge state switching was previously observed in photoluminescence experiments for the divacancy defect in 4H-SiC. The participating dark charge state could not be identified with certainty. We use constrained DFT to investigate the mechanism of charge state conversion from the bright neutral charge state of the divacancy defect to the positive and negative charge states including corresponding recovery of the neutral charge state. While we can confirm that the positive charge state is dark, we do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
(118 reference statements)
1
6
2
Order By: Relevance
“…1B, inset) (32). The location in depth of the observed defects is consistent with isolation to the i-type layer, as expected from formation energy calculations (35) and the local Fermi level (36). This depth localization provides an alternative to delta-doping (37), which is not possible with intrinsic defects, facilitating positioning and control in fabricated devices ( Fig.…”
Section: Isolated Single Defects In a Semiconductor Devicesupporting
confidence: 83%
See 1 more Smart Citation
“…1B, inset) (32). The location in depth of the observed defects is consistent with isolation to the i-type layer, as expected from formation energy calculations (35) and the local Fermi level (36). This depth localization provides an alternative to delta-doping (37), which is not possible with intrinsic defects, facilitating positioning and control in fabricated devices ( Fig.…”
Section: Isolated Single Defects In a Semiconductor Devicesupporting
confidence: 83%
“…while it is less consistent with a recently proposed three-photon model converting to VV + (35,55). Further study of the spin dependence of this ionization may lead to the demonstration of spin-to-charge conversion in VV 0 .…”
Section: Charge Gating and Photodynamics Of Single Defectscontrasting
confidence: 67%
“….0 2 ( R T ) [22] 637 [61] 10 6 [ 226] 0.1 [ 226] 3-5 0.04 [ 176] 0.4 [ 195] C S i V − 1.4-2.1 [82] 0.04 (4 K) [75] 738 [73] 10 6 [73] 0.1 [73] 70 [21] 0.37 [ 197] C G e V − 1.9-2.7 [82] 0.1 (5 K) [81] 602 [80] 0.05 [80] 70 [80] SiC V − Si 1.2-2.5 [ 41,42] 20 (17 K) [ 227] 858-916 [94] 10 4 [52] 0.25 [27] 6-9 [97] 3 [ 158] 26 [ 201] SiC [44] 64 (5 K) [ 117] 1078-1134 [84] 10 5 [56] 0.06 [56] 3-6 [56] 2.5 [28] SiC [45] 640-680 [87] 10 6 [87] 0.1 [87] h-BN 560-780 [ 132] 10 6 [ 228] 0.08 [ 229] 81 [ 134] 15 [ 185] 65 [ 202] WSe 2 730-750 [ 132] 0.12 [ 204] 21 [ 230] 18…”
Section: Hostmentioning
confidence: 99%
“…These energy levels represent charge‐state transitions, where the defect may capture holes or electrons from the valence or conduction bands, respectively. Example point defects are shown for the case of 4H‐SiC in Figure a, including the Si vacancy (VSi), [ 41,42 ] C vacancy (VC), [ 43 ] divacancy (VSiVC or VV), [ 44 ] C antisite‐vacancy pair (CSiVC or CAV), [ 45 ] nitrogen‐vacancy center (NCVSi or NV) [ 46 ] and vanadium impurity (V). [ 47,48 ]…”
Section: Point Defects As Quantum Contendersmentioning
confidence: 99%
“…cess may lead to a dark state, i.e., a permanent loss of qubits [33][34][35]. The qubit state can be restored by applying ∼1.3 eV optical excitation [33][34][35], where the nature of the dark state was debated in the literature [33,34,50]. According to one of the most recent study [35], the dark state can be identified as the negative charge state of divacancies where optical excitation at ∼1.25 eV is the threshold of photoionization of the electron from the ingap defect level to the conduction band edge at cryogenic temperatures.…”
mentioning
confidence: 99%